Investigation of in vitro antioxidant and cytotoxic properties of Lagerstroemia thorelli leaf extract - Lihu, Imanul Kabir (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.